Empowering Coastal Communities Through Ecotourism: Enhancing Economic Livelihoods And Turtle Conservation Efforts - Luluk Fadliyanti; Diswandi Diswandi; Muhammad Dzul Fadlli; Vici Handalusia; Muhamad Bai’ul Hak; Nadia Nuril Ferdaus; Bakti bin Hasan Basri; Wan Roshidah binti Fadzim; Judandi Rizky Pratomo; Widyatul Jannah (International Journal Of Community Service, 2024)
This community engagement project aimed to empower coastal communities through ecotourism while enhancing sea turtle conservation in Nipah, North Lombok, Indonesia. Conducted in collaboration between Mataram University and Universiti Utara Malaysia, the program combined educational sessions, interactive discussions, and symbolic hatchling releases to foster environmental awareness and sustainable livelihoods. Participants gained valuable insights into sea turtle life cycles, threats, and the importance of community-driven conservation. The event successfully strengthened public commitment to biodiversity protection and promoted Nipah as a model for eco-tourism development. Moreover, the initiative demonstrated how integrated conservation and tourism strategies can contribute to marine ecosystem restoration and socio-economic resilience in coastal areas.